2000
DOI: 10.1046/j.1464-410x.2000.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of urge urinary incontinence in women: a systematic review of randomized clinical trials

Abstract: Objective To assess the ef®cacy of physical therapies for ®rst-line use in the treatment of urge urinary incontinence (UUI) in women, using a systematic review of randomized clinical trials (RCTs). Materials and methods A computer-aided and manual search was carried out for RCTs published between 1980 and 1999 investigating the treatment of UUI de®ned by the keywords`physical therapies', e.g. bladder (re)training (including`behavioural' treatment), pelvic¯oor muscle (PFM) exercises, with or without biofeedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(91 citation statements)
references
References 64 publications
(109 reference statements)
1
85
0
5
Order By: Relevance
“…92,93 From a health service perspective it is important to balance short-and long-term effectiveness against the potential adverse events and costs. Compared with surgical treatments, non-surgical treatments, such as lifestyle changes and physical therapies (such as PFMT), are associated with limited side effects and do not preclude future changes in management.…”
Section: Chaptermentioning
confidence: 99%
“…92,93 From a health service perspective it is important to balance short-and long-term effectiveness against the potential adverse events and costs. Compared with surgical treatments, non-surgical treatments, such as lifestyle changes and physical therapies (such as PFMT), are associated with limited side effects and do not preclude future changes in management.…”
Section: Chaptermentioning
confidence: 99%
“…Basicamente, seu objetivo é inibir a contração involuntária do detrusor 10 . Diversos estudos 3,11,12 verificaram boa efetividade no tratamento da BH com a utilização da eletroestimulação transvaginal (ET).…”
Section: Introductionunclassified
“…By means of audible or visual biofeedback, the patient acquires information on the physiological process of contraction, which was unknown in most cases until then (27). Aukee et al (28) observed significant improvement in the strengthening of the PF muscle in women with UI who had undergone biofeedback and kinesiotherapy treatment, within a twelve-year period.…”
Section: Methodsmentioning
confidence: 99%